Cavernous hemangioma presented with gigantic tongue (Bangladesh Journal of Medical Science, 2015)
Lingual hemangioma is a benign congenital vascular tumour that may cause macroglossia. It can present with airway obstruction, speech disturbance, swallowing difficulties and mandible dental deformities. It usually occurred during childhood. Females are more affected. It usually poses difficulties in diagnosis and management. This case illustrated a rare case of lingual hemangioma in a 5 year old boy presented with tongue enlargement associated with swallowing difficulties and significant tongue bleeding which required blood transfusion. Surgical intervention in the form of tongue reduction surgery was successfully done to him. Histopathological examination revealed a cavernous hemangioma.Bangladesh Journal of Medical Science Vol.14(4) 2015 p.405-408